Food security: the challenge of feeding 9 billion people. - Godfray, H; Beddington, JR; Crute, I; Haddad, L; Lawrence, D; Muir, J; Pretty, J; Robinson, S; Thomas, S; Toulmin, C (2010)
Continuing population and consumption growth will mean that the global demand for food will increase for at least another 40 years. Growing competition for land, water, and energy, in addition to the overexploitation of fisheries, will affect our ability to produce food, as will the urgent requirement to reduce the impact of the food system on the environment. The effects of climate change are a further threat. But the world can produce more food and can ensure that it is used more efficiently and equitably. A multifaceted and linked global strategy is needed to ensure sustainable and equitable food security, different components of which are explored here.